Design of an Electromechanical Testing Machine for Elastomers’ Fatigue Characterization - Gabriel Testa; Nicola Bonora; Luca Esposito; Gianluca Iannitti (Engineering Proceedings, 2025)
The VITAL-E (Versatile Innovative Testing Low-Cycle Fatigue for Elastomers) project introduces a shift in low-cycle fatigue (LCF) testing by replacing traditional hydraulic systems with an electromechanical solution. Hydraulic machines, although widely used, present issues such as fluid leakage, environmental impact, high maintenance, and complex feedback control. In contrast, VITAL-E incorporates a zero-backlash linear actuator, addressing a key challenge in electromechanical systems: backlash. This issue, caused by axial movement between the nut and screw during load reversals, can disrupt load application and compromise test accuracy. By eliminating backlash, the chosen actuator ensures continuous and precise load application, especially during critical cycle reversals, enhancing both the accuracy and reliability of LCF testing. Beyond technical improvements, the electromechanical system reduces component complexity, wear, and maintenance needs while offering easier upgrades and adaptability to evolving testing demands. Compared to conventional hydraulic systems, VITAL-E’s design offers an innovative industrial solution, promoting a new generation of LCF test machines that excel in accuracy, reliability, and operational efficiency. This innovation aligns with the growing demand for sustainable and adaptable testing solutions, particularly in the automotive industry, ensuring that LCF testing remains relevant for future research and industrial needs.